Disorders in brassinosteroids signal transduction triggers the profound molecular alterations in the crown tissue of barley under drought - Anetta Kuczyńska; Martyna Michałek; Piotr Ogrodowicz; Michał Kempa; Paweł Krajewski; Vladimiro Cardenia; Maria Teresa Rodriguez-Estrada; Marina Pérez-Llorca; Sergi Munné-Bosch; Krzysztof Mikołajczak (PLoS ONE, 2025)
The advanced molecular tools provide critical inputs in uncovering the regulatory mechanisms underlying plants’ adaptation to abiotic stress. Presented holistic studies were done on the barley crown tissue being essential for plant performance under various environmental stimuli. To investigate the effect of brassinosteroids (BRs), the known players in stress management, on molecular response of this tissue to drought, the genotypes with different BRs signal transduction efficiency were employed. Large-scale transcriptomic and proteomic profiling confirmed the specific re-modeling of behavior of the BRs-insensitive barley uzu1.a mutant under drought. On the other hand, a set of genes expressed independently of the genotype was identified, including dehydrin encoding genes. This study also uncovered the candidate genes to be linkers of phytohormones crosstalk. Importantly, we detected the converging upregulation of several proteins and encoding genes under drought, including late embryogenesis abundant proteins and chaperones; they represent a promising target for cereals’ improvement. Moreover, the greatest variation between genotypes in accumulation of BRs in the crown tissue exposed to drought was observed for castasterone. Presented multi-omics, high-throughput results enhanced the understanding of molecular response to drought in crown tissue. The new insight was provided into the relationships between gene expression, protein and phytohormone content in barley plants of different BRs signaling.